Neuroticism Predicts a Long-Term PTSD After Earthquake Trauma: The Moderating Effects of Personality - Yin, Qianlan; Wu, Lili; Yu, Xiaoqian; Liu, Weizhi (Frontiers in Psychiatry, 2019)
Background: The devastating 8.0 magnitude Wenchuan earthquake which killed nearly 90,000 people in western China, the heartache is still being felt despite the large-scale recovery and reconstruction of the affected areas. This study investigated the relationships of earthquake-trauma exposures and personality with posttraumatic stress disorder (PTSD), to identify the long-term consequences of Wenchuan earthquake on the survivors and the risk factors related to chronic PTSD. We hope the findings can contribute to develop new health care prevention and interventions for the survivors. Methods: We collected a sample of 490 people about 3 years after the Wenchuan earthquake, using questionnaires about demographic information and the traumatic experience in earthquake, the Impact of Event Scale-Revised (IES-R), and the Eysenck Personality Questionnaires(EPQ), to find the consequences of Wenchuan earthquake on the survivors and the potential factors related to the long-term morbidity of PTSD. Result: Traumatic experiences, such as witnessing someone being seriously injured, having your house seriously damaged, and having close relatives injury severely, were associated with developing PTSD. Personality measured by EPQ was also closely related to PTSD. Regression analyses indicated that a potential linear model characterized the relationship between PTSD, neuroticism and psychoticism, yet extraversion/introversion are not significant factors. In the multivariate logistic regression, neuroticism (a continuous variable measured by EPQ) was of more significance in predicting the morbidity of long-term PTSD, compared with other variables (odds ratio (OR) = 1.113, 95% confidence interval (CI) =1.081-1.146 , Wald Value=50.467, P<0.001). The final path diagram built a model indicated the moderating role of personality in the relationship between traumatic experiences and PTSD (CMIN/DF=2.324, P<0.001; CFI=0.879<0.8; RMSEA=0.05<0.08). Conclusion: This study demonstrated that the role of personality traits and subjective exposure experiences in the vulnerability associated with PTSD after earthquake. Among all the personality traits, neuroticism is considered a vulnerability factor of PTSD, and other personality traits also moderate the effects of traumatic experiences associated with PTSD. These findings might be useful for psychologists to develop intervention strategies for people suffered natural disasters, and to help individuals with PTSD to heal fully.